Hybrid CNN-LSTM and Cox Model for Bipolar Risk Analysis Using Social Media Data - Amanda, Rizki; Aulia, Jasmine (Indonesian Journal of Data and Science, 2025)
Introduction: Mental disorders such as bipolar disorder are becoming increasingly prominent, particularly with the rise of emotional expression through social media. Early detection remains a significant challenge due to the lack of non-invasive, real-time assessment methods. Methods: This study proposes a hybrid deep learning approach combining Convolutional Neural Network–Long Short-Term Memory (CNN-LSTM) and the Cox Proportional Hazards (Cox PH) model to analyze the risk and timing of bipolar disorder onset. A dataset of 3,511 tweets from 517 Twitter users was collected. The CNN-LSTM model classified bipolar risk levels based on text data, while the Cox PH model estimated the time-to-event for high-risk conditions using behavioral features and predicted risk labels. Results: The hybrid model demonstrated strong predictive performance. The risk label significantly influenced the time to high-risk condition (hazard ratio = 5.39, p < 0.005). The model achieved a concordance index (C-index) of 0.816, indicating high reliability in survival prediction. Conclusions: This case study highlights the potential of integrating deep learning and survival analysis for early bipolar disorder detection using social media data. The proposed non-invasive method can support mental health monitoring while raising awareness of ethical and privacy considerations